Intrinsically conducting polymer (ICP) coated aramid fiber reinforced composites for broadband radar absorbing structures (RAS). (28th July 2021) - Kim, Chingu; Kim, Minkook
Abstract: In this study, a composite radar absorbing structure (RAS) was developed using intrinsically conducting polymer (ICP)-coated aramid fiber reinforced polymer composites (AFRPs). Dielectric aramid fibers fabric were fabricated by simple dip-coating with PEDOT:PSS and PANI:CSA conducting polymers. The electrical conductivity, dielectric constant, radar absorbing performance in the X-band range (8–12 GHz) and mechanical properties of the ICP-coated AFRP RAS were investigated with respect to the type and composition ratio. As a result, the optimal type and composition ratio of the ICPs were presented. The facile process of the ICP coating on the reinforcing fibers will help further the exploitation of conducting polymers for RAS. Graphical abstract: Image 1